Two retarded male cousins with odd facies, hypotonia, and severe constipation: possible examples of the X linked FG syndrome. Issue 2 (April 1983) - Burn, J; Martin, N
Abstract : A boy was referred in 1977 for investigation of global retardation and hypotonia. Minor dysmorphic features and intractable constipation were noted. In 1981 the mother's sister had a son with a similar phenotype. This is probably the X linked Opitz-Kaveggia or FG syndrome.